EKONOMI POLITIK IKLAN DI INDONESIA TERHADAP KONSEP KECANTIKAN - Goenawan, Felicia (Scriptura, 2007)
One of media to establish woman image was by means of media%2C either television%2C radio%2C or print media. The media content that was primary highlighted by feminism communities was advertisement. Advertising presentation on television and print media contributed to significant effects in depiction of woman image. The political economic approach strove to explain in view of a big representation such as general effects of political economy in societies or effects of power holders on definition of events that became news. It was due to control against news contents or news considered important and unimportant. Whoever had more economic power was the one who could control the media. It was not surprising that nowadays media roles here became a means to legitimize class interests that had and controlled media through production of awareness and fake reportage on objective realities that had biased due to be followed by interests both politically and economically Abstract in Bahasa Indonesia : advertisements%2C print media%2C political economic approach